Children, technology and healthy development : how to help kids be safe and thrive online - Knibbs, Catherine (New York : Routledge, 2022)
"How can adults keep children safe and healthy online now and in the future? How can we thrive alongside technology? This highly accessible book unpacks the latest psychological research, attachment theory and neurobiology to offer parents and professionals insight into how technology impacts children's development, and how to navigate our lives online. Cath Knibbs shares her extensive experience to reveal what we know about human behaviour in cyberspace, and particularly that of children using devises, consoles and social media platforms. She offers deeper understanding of how and why children engage online and shows parents and professionals how, rather than being overwhelmed by the dangers and pathologies of cyberspace, we can learn to support children in using technology healthily. She covers key topics including social media use and abuse, impact of screen time, issues round gaming, and extreme behaviours online. By the end of this book you will be able to understand your child better, and have an understanding of what is happening in their minds, brains and bodies in relation to the technological and digital world. Children, Technology and Healthy Development is for all parents, and professionals in psychology, education, social care and the police who are concerned with understanding how we support children in an online world. It will also be valuable reading for those in tech design interested in the impact of technology on the developing human"--
SECTION 1. THE THEORY OF HUMAN DEVELOPMENT IN A WORLD OF TECHNOLOGY: Attachment, trauma and child development in an exponential technological age -- Attachment and infancy, the foundation of our behaviour and development -- Trauma, a very basic introduction -- E-ttachment and the developing child -- The neurobiology of online behaviour. A new proposition -- Biology before brain, why states precede disinhibition online -- Addiction, attachment or something else? What is the problem? -- Parenting and professional understanding of children with, around and through technology -- SECTION 2. GAMING: PITFALLS, POSITIVES AND PROCESSES. HOW TO HELP. Gaming; good, bad or the problem? From play to time limitations -- Gaming issues, risks and pitfalls -- Abuse in gaming; from bullying to exploitation -- It's not all bad, examples from practice -- Gambling in games, is this the same as sticker books, competition or is it more sinister? -- SECTION 3. SOCIAL MEDIA: RELATIONSHIPS IN THE PALM OF YOUR HAND. THE WHAT, WHY AND HOW TO HELP. Does technology, social media or our devices have an impact on mental health? -- Social media and dis-order -- Just what is social media and what is it for? -- Social behaviour in an online world, parenting and child development -- Who, what, why, when and the how of social media, and the new communication language -- Social, communication and attachment media. An online SCAM?
Keywords: Internet and children; Child development; COMPUTERS / General; COMPUTERS / Computer Literacy; COMPUTERS / Educational Software